PENGETAHUAN MODERASI BERAGAMA KELAS IX DI PONDOK PESANTREN ATS TSAQOFIY TANJUNG MORAWA - Lisa Wardani (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
The main problem of this research, discusses "Knowledge of Religious Moderation Class VI at Ats Tsaqofiy Islamic Boarding School Tanjung Morawa". The main problems of the research are divided into two sub-problems, namely: 1) What is the Meaning of Religious Moderation in Indonesia, 2) How is Knowledge of Religious Moderation among Santri Class VI Pesantren Ats Tsaqofiy Tanjung Morawa. The objectives of this research are: 1) To find out the Purpose of Religious Moderation in Indonesia, 2) To find out the Level of Knowledge of Religious Moderation among Pesantren Ats Tsaqofiy Tanjung Morawa. This type of research is quantitative, with a normative theological approach. The sources of research data are primary data, data obtained using questionnaires, and several other community leaders. Second, from several books, journals, magazines, newspapers or online news. Supporting data are not taken directly from informants but through documents and research results that are relevant to this research problem to complete the information needed in the study. The results of this study can be seen that most of the respondents have a "sufficient" level of knowledge about religious moderation as many as 15 people (48.4%) and respondents have a "less" level of knowledge about religious moderation as many as 12 people (38.7%), and respondents have a "good" level of knowledge about religious moderation as many as 4 people (12.9%). So, according to Ari Kunto, the measurement of the level of knowledge about religious moderation in class VI students is categorized as "less" because the percentage of research results above is less than 55% (<55%).